The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12124861
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Climate Change Risk: A Content Analysis of IPCC’s Summary for Policymakers

Abstract: This study investigated the effectiveness of climate change risk communication in terms of its theoretical potential to stimulate recipients’ awareness and behavioral change. We selected the summary for policy makers (SPM) of the most recent Intergovernmental Panel on Climate Change (IPCC) report in order to conduct a content analysis; the extended parallel process model and construal level theory served as conceptual lenses to perform the analysis. Specifically, we evaluated to what extent the SPM included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…The perception of environmental quality issues depends on many factors, both social and individual characteristics of people. The importance of ecological education and shaping pro-ecological attitudes are emphasized [54,[64][65][66][67][68]. Similar relationships have been identified in studies conducted in southeastern Poland.…”
Section: Discussionsupporting
confidence: 62%
“…The perception of environmental quality issues depends on many factors, both social and individual characteristics of people. The importance of ecological education and shaping pro-ecological attitudes are emphasized [54,[64][65][66][67][68]. Similar relationships have been identified in studies conducted in southeastern Poland.…”
Section: Discussionsupporting
confidence: 62%
“…While a combination of threat and efficacy beliefs appears to increase the likelihood that a person will take actions to address climate change, there is clear evidence that a balance between threat and efficacy has not been achieved in climate change communications to date. Analysis of the Summary for Policymakers (SPM) of the Synthesis Report (SYR) of the IPCC Fifth Assessment Report (AR5) has shown that threat information occurred much more frequently than efficacy-based information, with the latter tending to feature later on in the document (Poortvliet et al 2020). Efficacy content that was included in the SPM tended to refer to actions yet to be taken, rather than evidence of past successes.…”
Section: Why Climate Communicators Must Address Efficacy Nowmentioning
confidence: 99%
“…These websites were highlighting that the service were not only eco-friendly but could also have a severe impact in favor of the environ ment. In order to explain these arguments, different sections, or even blog posts, wer The current study is inspired by previous papers [1,10,33,50] that are related to sustainability studies and employed content analysis [51][52][53]. The current research is highlighting the need for a better understanding of the green practices and how this green tradition is communicated through the green hosting companies in the era of big data, during which there is an urgent need for sustainable development and a reduction of the energy consumption used for the IT services.…”
Section: Green Hosting As An Important Part Of the Servicesmentioning
confidence: 99%